The Efficacy and Mechanism of Chinese Herbal Medicines in Lowering Serum Uric Acid Levels: A Systematic Review - Chen, Liqian; Luo, Zhengmao; Wang, Ming; Cheng, Jingru; Li, Fei; Lu, Hanqi; He, Qiuxing; You, Yanting; Zhou, Xinghong; Kwan, Hiu Yee; Zhao, Xiaoshan; Zhou, Lin (Frontiers in Pharmacology, 2021)
Background. Chinese herbal medicines are widely used to lower serum uric acid levels. However, no systemic review summarizes and evaluates their efficacies and the underlying mechanisms of action. Objectives. To evaluate the clinical and experimental evidences for the effectiveness and the potential mechanism of Chinese herbal medicines in lowering serum uric acid levels. Methods. Four electronic databases PubMed, Wed of Science, the Cochrane Library and Embase were used to search for Chinese herbal medicines for their effects in lowering serum uric acid levels, dated from 1 January 2009 to 19 August 2020. For clinical trials, randomized controlled trials (RCTs) were included; and for experimental studies, original articles were included. The methodological quality of RCTs was assessed according to the Cochrane criteria. For clinical trials, a meta-analysis of continuous variables was used to obtain pooled effects. For experimental studies, lists were used to summarize and integrate the mechanisms involved. Results. A total of 10 clinical trials and 184 experimental studies were included. Current data showed that Chinese herbal medicines have promising clinical efficacies in patients with elevated serum uric acid levels (SMD: -1.65, 95% CI: -3.09 to -0.22; p = 0.024). There was no significant difference in serum uric acid levels between Chinese herbal medicine treatments and Western medicine treatments (SMD: -0.13, 95% CI: -0.99 to 0.74; p = 0.772). Experimental studies revealed that the mechanistic signaling pathways involved in the serum uric acid lowering effects include uric acid synthesis, uric acid transport, inflammation, renal fibrosis and oxidative stress. Conclusions. The clinical studies indicate that Chinese herbal medicines lower serum uric acid levels. Further studies with sophisticated research design can further demonstrate the efficacy and safety of these Chinese herbal medicines in lowering serum uric acid levels and reveal a comprehensive picture of the underlying mechanisms of action.